Assessing of The Continuance Intentions to Use Fintech Payments, an Integrating Expectation Confirmation Model - Nurdin, Tubagus Asep; Alexandri, Mohammad Benny; Sumadinata, Widya; Arifianti, Ria (Journal of Applied Data Sciences, 2023)
This study aims to identify the factors influencing users' continuance intention to use FinTech payment applications. An online questionnaire was administered to 361 FinTech users during the pandemic using Google Forms to achieve the objective. The Expectation-Confirmation Model (ECM) was extended to include perceived trust, social influence, and functional benefits and was used to analyze the data obtained from the survey. The study results indicate that prior expectation confirmation and perceived usefulness of the application after use are crucial for increasing users' continuance intention to use the service. Additionally, perceived trust and social influence positively influence users' continuance intention to use the service and can be strengthened through personalized experiences and positive interactions. This study provides valuable insights for researchers and practitioners in the field of FinTech payments.